Physicochemical exfoliation of graphene sheets using graphitic carbon nitride. (2nd October 2019) - Priyanka, V.; Savithiri, G.; Subadevi, R.; Suryanarayanan, V.; Sivakumar, M.
Abstract : The development of methods for the synthesis of graphene on a large scale at an affordable cost using less toxic materials has attracted significant interest in recent years. Abstract : The development of methods for the synthesis of graphene on a large scale at an affordable cost using less toxic materials has attracted significant interest in recent years. This study sheds light on the synthesis of graphene by a simple physicochemical technique. Graphene has been exfoliated from graphite using graphitic carbon nitride as a milling agent, which has the ability to cleave the C–C bonds. The intensity band ratio ( I D / I G ) has been calculated to be 1.01 via Raman spectroscopy, indicating that the graphene sheet has few layers; transmission electron microscopy images indicate that the transparent and few layers of graphene sheet have been well exfoliated without any pleats. Atomic force microscopy indicated that the thickness of the graphene sheet was 3–4 nm, and the lateral size was 1.5–2.5 μm. X-ray photoelectron spectroscopy strongly revealed the C–C sp 2 hybridization of graphene. Moreover, the specific surface area was found to be 969 m 2 g −1, which was thousand times greater than that of commercial graphite. Thus, this exfoliated graphene has good conductivity, which will be suitable for electrochemical applications.